EFFECT OF ARM MUSCLE POWER AND BALANCE ON PASSING ABILITY ON FOOTBALL STUDENTS IN CLASS XI UPT SMAN 10 ENREKANG - Nur, Muhammad Nur; Dos Santos, Hezron Ahlim; Dos Santos, Maria Herlinda (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
The research aims to determine: (1) The influence of arm muscle power on overhead passing ability, (2) The influence of balance on overhead passing ability, (3) the difference in more effective influence between arm muscle power and balance Enrekang students. Experimental research with the research design used, namely pretest-posttest. The population used in this research was class XI UPT SMAN 10 Enrekang students with a total of 20 students. Sampling used the proportional sampling technique. The group division in this research is ordinal pairing. For the arm muscle power training group and the balance training group. The research results show that: (1) There is an influence of arm muscle power on students' volleyball passing ability with a calculated t value of 12.555 > t table 1.833, and a significant value of 0.000 < 0.05, (2) There is an influence of balance on volleyball passing ability with t calculated value 9.043 > t table 1.833, and significance value 0.000 < 0.05, (3) There is a difference in the influence of arm muscle power and balance on students' volleyball passing ability with t calculated value 1.936 > t table 1.734 and sig. 0.085 > 0.05, the difference in the posttest mean value is 1.00.